Early pregnancy diagnosis in cows - Araújo, Paulo Graça; Pizelli, Gelio Nogueira; Carvalho, Mauro Ribeiro de; Resende, Osvaldo de Almeida; Carvalho, Luiz Ferreira de (Pesquisa Agropecuaria Brasileira, 2014)
Early diagnosis of pregnancy was studied in 153 clinically normal cows. Seventeen days after insemination, two levels of estrogenic hormone (5 and 10 mg) were subcutaneously injected into 76 animals. The remaining animals were considered as checks. Cows without heat expression five days after the treatment were considered pregnant. This diagnosis was confirmed by palpation 45 and 60 days later. Estrogenic hormone was not considered efficient for early diagnosis of pregnancy, since the results obtained with treatment were no different from the control. These results are somewhat in conflict with those of other authors.